2020
DOI: 10.24912/jmbk.v4i2.7523
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Strategi Pengembangan SDM Terhadap Kinerja Karyawan

Abstract: This research aims to determine the effect of training, work dicipline and organization communication toward employee performance. The sample used in the study amounted to 158 employees. The research method uses multiple linear regression analysis with the help of managing data using SPSS version 22 software. The results of this study indicate that training, organization communication partially have a significant effect on the employee performance, and work dicipline partially haven’t a significant effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Meyer (2015) believes that work discipline is considered an important part of employee performance. Daud et al (2013) in a study clarified that discipline has a significant effect on employee performance, while Widjaja & Supriyatna (2020) concluded that discipline has no significant effect on employee performance.…”
Section: Resultsmentioning
confidence: 99%
“…Meyer (2015) believes that work discipline is considered an important part of employee performance. Daud et al (2013) in a study clarified that discipline has a significant effect on employee performance, while Widjaja & Supriyatna (2020) concluded that discipline has no significant effect on employee performance.…”
Section: Resultsmentioning
confidence: 99%